CONSCIOUSNESS AND PRECAUTIONARY HABIT RELATING TO COVID-19 INFECTIONS AMONG STUDENTS IN NWAFOR ORIZU COLLEGE OF EDUCATION, NSUGBE - STELLA, NWANKWO NONYELUM (Innovare Journal of Life Sciences, 2021)
Objective: Similar to outbreaks of many other infectious diseases, success in controlling the novel coronavirus infection requires a timely and accurate monitoring of the epidemic. The main objective of the present study is to assess consciousness and precautionary habit relating to COVID-19 infections among students. Methods: The descriptive survey research design method was used. The researcher formulated two research questions. A self-developed questionnaire was adopted for data collection. The sample size consists of students in Nwafor Orizu College of Education, Nsugbe, selected using purposive random sampling technique, subsequently, thirty copies of the questionnaire were administered by the researcher. Mean and standard deviation were used to analyze the data. Results: The study showed among other findings that students are conscious about the possibility of the disease transmission by droplets when an infected person cough, sneezes, or speaks. These findings have the vantage of providing the researchers, government, students, policy makers, and government with adequate and correct baseline data on consciousness and precautionary habit relating to COVID-19 infections among students. Conclusion: Based on the research findings, it was concluded that the world has a long history of successful efforts to prevent or cure widespread infections. The main points in preventing the spread in society are hand hygiene, social distancing, and quarantine. With increased testing capacity, detecting more positive patients in the community will also enable the reduction of secondary cases with stricter quarantine rules.